(untitled) (Medical Forum Monthly, 2020)
Objective: To study the cytopathalogical pattern of breast lumps in relation to the clinical findings above 25 years of female. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Surgical Department of Allama Iqbal Memorial Teaching Hospital Sialkot from 1stJan 2014 to Dec 2018. Materials and Methods: A total of 2000 breast lump patients visited the OPD, only 325 of which have been diagnosed from 2014 to 2018 in 40.21 mean age group same for four years. Results: A total of 325 cases were studied, with the mean age of 40.21 years; the most involved site was left (52%) as compared to right (47.06%).The commonest lesions in descending order were fibroadenoma (56%), carcinoma (27%) and abscess(14%). The data was analyzed through SPSS 20. Conclusion: The commonest cytopathalogical lesion is fibroadenoma, followed by carcinoma. Early detection and diagnosis is required to reduce mortality and morbidity significantly.